Penegakan Hukum Tindak Pidana Kekerasan Dalam Rumah Tangga Diwilayah Hukum Kepolisian Sektor Kuantan Tengah Kabupaten Kuantan Singingi - Mambela, Febri; Shilvirichiyanti, Shilvirichiyanti; Aprinelita, Aprinelita (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2022)
Law enforcement against criminal acts of domestic violence in the jurisdiction of the Central Kuantan Sector Police takes preventive measures, namely seeking peace or mediation to the parties by providing input and solutions to problematic parties and socializing law number 23 of 2004 concerning the elimination of domestic violence. domestic violence and repressive actions such as investigation, investigation, arrest, detention, search, confiscation, and submission of case files. Inhibiting Factors in Law Enforcement of Domestic Violence in the Police Legal Area of ​​Central Kuantan Sector, namely Legislation Factors, Law Enforcement Factors, Facilities and Infrastructure Factors.